Minor modifications to ceritinib enhance anti-tumor activity in EML4-ALK positive cancer. Issue 2 (1st May 2016) - Kang, Chung Hyo; Kim, Eun-Young; Kim, Hyoung Rae; Lee, Chong Ock; Lee, Heung Kyoung; Jeong, Hye Gwang; Choi, Sang Un; Yun, Chang-Soo; Hwang, Jong Yeon; Lee, Joo-Youn; Son, You Hwa; Ahn, Sunjoo; et al.
Highlights: We synthesized an excellent ALK inhibitor, KRCA-386, structurally similar to ceritinib. KRCA-386 shows improved efficacy in vitro and in vivo compared to ceritinib. KRCA-386 has better inhibitory activity than ceritinib against crizotinib-resistant mutants, especially G1202R. KRCA-386 has higher penetration activity through the blood brain barrier than ceritinib. KRCA-386 inhibits multi-kinases including ALK as to contribute to the excellent in vivo efficacy. Abstract: Ceritinib, an ALK inhibitor, was hurriedly approved by the US FDA last year, and demonstrates impressive results in EML4-ALK positive patients. To get a superior ALK inhibitor, we synthesized several ceritinib derivatives with minor modifications to the phenylpiperidine moiety. Biochemical and cellular assays demonstrated the improved activity of KRCA-386 over that of ceritinib. KRCA-386 has superior inhibitory activity against ALK mutants commonly found in crizotinib-resistant patients. Particularly, KRCA-386 has considerably greater activity than ceritinib against the G1202R mutant, one of the most challenging mutations to overcome. The cell cycle analysis indicates that ALK inhibitors induce G1/S arrest, resulting in apoptosis. The in vivo xenograft data also demonstrate that KRCA-386 is significantly better than ceritinib. KRCA-386 dosed at 25 mpk caused 105% tumor growth inhibition (TGI) compared to 72% TGI with ceritinib dosed at 25 mpk. ( n = 8, P = 0.010) The kinase profiling assay revealed that several kinases, which are known to be critical for tumor growth, are inhibited by KRCA-386, but not by ceritinib. We anticipate that this characteristic of KRCA-386 enhances its in vivo efficacy. In addition, KRCA-386 shows excellent blood brain barrier penetration compared to ceritinib. These results suggest that KRCA-386 could be useful for crizotinib-resistant patients with brain metastases.